The effect of breakfast on childhood obesity: a systematic review and meta-analysis - Wang, Kun; Niu, Yifan; Lu, Zhenzhen; Duo, Boyang; Effah, Clement Yaw; Guan, Lina (Frontiers in Nutrition, 2023)
Previous cohort trials have shown that skipping breakfast increases the risk of obesity or overweight in children. However, this finding remains controversial. Through a meta-analysis, this study systematically evaluated the effect of skipping breakfast on the prevalence of obesity or overweight in children.We performed a literature search for studies published until March 19, 2023. using the Cochrane, PubMed, and Embase databases. Based on the inclusion and exclusion criteria, observational studies on the relationship between skipping breakfast and overweight/obesity in children and adolescents were analysed. Three investigators independently screened the relevant literature, extracted the data, and assessed the risk of bias. The quality of the included studies was assessed using the Newcastle-OttawaScale (NOS). A random-effects model was used. The odds ratio (OR) with its 95% confidence interval (CI) was used to indicate the effect size.RESULTS: A total of 40 retrospective studies with 323244 children ranging in age from 2-20years were included in this study. The results of this meta-analysis showed that children and adolescents who skipped breakfast had a significantly higher prevalence of obesity or overweight than those who ate breakfast (OR, 1.59;95% CI, 1.33-1.90; P<0.001). Skipping breakfast was positively associated with overweight in children and adolescents (OR, 1.37; 95% CI, P<0.001). Similarly, skipping breakfast was positively associated with obesity in children and adolescents (OR, 1.51; 95% CI, 1.30-1.76; P<0.001). The effect was also different by sex, with girls being the most affected (OR,1.47;95% CI, 1.23-1.76; P<0.001). There was also a correlation between skipping breakfast and abdominal obesity in children (OR, 0.65;95% CI, 0.55-0.77; P<0.001).This meta-analysis suggested that skipping breakfast is associated with an increased risk of overweight/obesity in children and adolescents. The findings provide support for a possible protective role of breakfast against excessive weight gain in children and adolescents. However, more rigorous study designs with validated and standardized measures of relevant variables are needed.